BODY CARE: CONTRIBUTIONS IN THE LIGHT OF AFRICAN ORIGIN (Fiep Bulletin - online, 2016)
Caring for the body is one of the key concerns of all professionals of Physical Education. The conference title this year inspires us to make a contribution to this body arising zeal of African origin. This article discusses nuances of African origin in the care of the body that go beyond the physical aspect, striving to other constitutive dimensions of the human essence. In this sense, think the issue corporeality in the light of Candomblé concerns the "union" healthy body - mind balanced.
Keywords: corporeality; religiosity; African origin